The Influence of the Implementation of Information Systems and Work Discipline on Employee Performance at PT. Laskar Teknik Indonesiaa - Mustapa, Zainuddin (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This study examines the influence of information system implementation and work discipline on employee performance at PT. Laskar Teknik Indonesia. Utilizing a quantitative research method, data were collected from 32 employees and analyzed using descriptive statistical techniques. The findings indicate that the implementation of information systems has a positive and significant effect on employee performance by providing relevant data and supporting efficient decision-making processes. Similarly, work discipline plays a crucial role in enhancing employee motivation and productivity. The study concludes that these two factors complement each other in improving overall organizational performance, aligning with previous research findings in various sectors.